Modelagem dos componentes do balanço hídrico e monitoramento da seca em bacia hidrográfica no bioma Caatinga - Silva, Glauciene Justino Ferreira da (2021)
In the semi-arid region of Brazil, droughts lead to water deficit and lack of freshwater, which makes determining the water balance an important issue. In the water balance, reliable estimation of actual evapotranspiration (ET) is essential for hydrological and ecological models, essentially in arid and semi-arid regions that are affected by droughts. The dynamics of ET in semi-arid river basins provide relevant information for water management during extreme drought events. However, the modeling of ET and water balance in these environments is an even greater issue. In this context, the general objective of this study is to estimate the components of the water balance and the ET to understand the spatiotemporal dynamics of drought in the Upper Paraíba river basin. The SWAT hydrological model was applied to estimate the water balance components. The simulation period lasted from January 1994 to December 2016. The SEBAL algorithm was applied to determine the ET during the period between 2005 and 2016. The drought indices Standardized precipitation index (SPI), Standardized soil index (SSI), Nonparametric multivariate standardized drought index (MSDIe), and the Parametric multivariate standardized drought index (MSDIp) were used to determine and analyze droughts from 2005 to 2016. The collected results from the hydrological modeling were classified as satisfactory, with Nash-Sutcliffe (NS) = 0.68 and coefficient of determination R2 = 0.69 (calibration), and NS = 0.7 and R2 = 0.68 (validation). Regarding the results of the water balance (surface runoff - SQ, and final soil water content - SW), the most vulnerable areas of the basin are those with high SQ rates and low SW. These zones are also the most degraded and are present in the central and eastern portions of the basin. As anticipated, the ET estimate demonstrated high variability in the entire data series, the highest values of actual ET occurred in the plant types of caatinga arboreal and arbustive- arboreal. Alterations in evapotranspiration behavior, surface temperature, and SAVI were observed through phenological changes in the caatinga vegetation according to the precipitation system. The use of variables obtained with SWAT and SEBAL for drought analysis presented satisfying results both in the spatialization of actual evapotranspiration anomalies (aETR), and the final soil water content (aSW) and in the graphs in which the negative deviations followed the periods of rainfall deficit in the basin. The conduct of the IAC, the drought indices SSI, SPI and MSDI satisfactorily identified the dynamics of drought during the period 2012−2016. Drought proportions were able to monitor the evolution of drought occurrences. Besides, the application of this methodology might raise awareness on public managers to comprehend future perspectives of drought occurrences, therefore, this information can help authorities in drought management.